MENINGKATKAN HASIL BELAJAR IPAS MATERI TRADISI KELUARGA DAN MASYARAKAT SEKITAR MELALUI LKPD BERBASIS KEARIFAN LOKAL PADA SISWA KELAS III SDN DALAM PAGAR ULU 2 - Siti Nor Halisa; Ria Mayasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of science and natural sciences in grade III, characterized by the learning outcomes of almost all students being low, namely below the criteria for achieving learning objectives set by the school. Likewise, teachers only use lecture methods rather than using media during learning. This research focuses on the use of local wisdom-based student worksheets (LKPD) in science learning on the topic of Family and Community Traditions. Based on these problems, the objectives to be achieved are (1) to determine the improvement of student learning outcomes using local wisdom-based student worksheets (LKPD), (2) to determine the implementation of local wisdom-based student worksheet media, (3) to determine student responses to local wisdom-based student worksheet media. The method used in this research is Classroom Action Research (CAR) adapting the Kemmis & MC Taggart model, consisting of two cycles and each cycle has four stages: initial planning, implementation, observation, and reflection. Data collection was carried out through tests (pretest and posttest), observation, student response questionnaires, and documentation. The subjects of this study were 15 third-grade students at SDN Dalam Pagar Ulu 2. The results of the study using local wisdom-based worksheets (LKPD) showed an improvement in the learning process. Learning outcomes in cycle I increased from 0% to 26%, and in cycle II from 46% to 87%. Learning implementation outcomes in cycle I, meeting 1, reached 71% and meeting 2, reached 86%. In cycle II, meeting 1 reached 72% and meeting 2, reached 91%. Student activity outcomes in cycle I, meeting 1 reached 60% and meeting 2, reached 83%. In cycle II, meeting 1 reached 66% and meeting 2 reached 91%. Student response outcomes reached 98%. Based on the results of the study, it can be concluded that learning using local wisdom-based worksheets can improve student learning outcomes. From the results of this study, there are several suggestions for school principals, teachers, and other researchers to be able to continue using or develop what has been done to obtain better results.